Assessment of health status, utilization, and out-of-pocket expenditure among the elderly in Ngestiharjo, Bantul, Yogyakarta - Hafidz, Firdaus; Monanda, Adelia Pramudita; Hariyanti, Tatik; Jamiah, Erni (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Background: As the population ages, it is increasingly crucial to develop community-centered health interventions. This study aims to describe and assess sociodemographic information, health characteristics, health utilization, and out-of-pocket expenses among older people in Ngestiharjo Village, Bantul, Yogyakarta. It was part of an initiative to empower community health workers to understand and address the health needs of older people. Methods: A cross-sectional survey was conducted from April to July 2023 involving 330 participants, with a targeted sample size of 356 elderly individuals. Data on sociodemographics, health status, health utilization, and expenditure were collected through interviews with older people or their companions. Results: Preliminary data showed that most participants were female (58.77%), married (64.91%), and primarily received health information from health workers (47.37%). Hypertension and joint and bone diseases were prevalent, with 16.67% likely experiencing depression. 11.4% of the respondents were hospitalized in the past year, with an average of 2.15 hospitalizations. Private hospitals (69.23%) were the most common healthcare facilities used for hospitalization, and 76.92% consistently utilized health insurance. The average out-of-pocket expenditure for hospitalization was 437,500 IDR. Community health centers (36.36%) and private hospitals (45.45%) were predominantly used for outpatient care, and 77.27% always used health insurance. The average out-of-pocket expenditure for outpatient care was 126,200 IDR. Conclusions: The study underscores the importance of empowering community health workers to effectively disseminate health information, fortify integrated health posts, manage common health issues, and tackle barriers to healthcare utilization and expenditures among older people.